Emergency Medical Service Planning - Ludmila Janosikova (Communications - Scientific letters of the University of Zilina, 2007)
The paper deals with emergency medical service planning using methods of mathematical programming. The goal is to offer a support tool to the health management evaluating the emergency system quality and efficiency. Mathematical models are implemented in the conditions of the Slovak Republic. Special attention is paid to the Zilina region.